Diseño de la galería principal de transporte de la mina Piedras Verdes, área minera Piedras Verdes 35 código 30000498, cantón Atahualpa, provincia de El Oro - Mendieta Cueva, Doménica Salomé (2023)
Currently, Piedras Verdes 35 mining project is in its initial stages, which is why an ex-ploratory gallery has been carried out in order to determine mineralized bodies that can be economically exploited. Since future production is not contemplated, it is necessary to adapt and determine a section that allows mechanization. For this reason, the present work "Design of the main transport gallery of the Piedras Verdes mine, Piedras Verdes 35 mining area, code 30000498', provided a proposal that allows fulfilling the mentioned purposes. The activities began with the characterization of the study area, which involved the topographic survey obtaining a length of 1056 meters of the exploratory gallery, where some vetiform structures are projected; in addition, it was proposed the franking of 300 meters to the north to intercept the mineralizations. In this way, the geology was defined, determining that in the surface layer, there is Quaternary material with a relative power of 14 meters; in-side the mine, there are areas of hydrothermal breccias, andesites, and granodiorites. On the other hand, when the rock massif was evaluated through Bienawski's RMR, three poor-quality sections were delimited and correlated with the Q index, where six sections of poor to mediocre quality were obtained. For the design, a section of 2.30 meters wide by 2.50 meters high is established, in the dimensioning, spaces for safety, personnel, machinery, drainage, and services are considered; thus, for the drilling and blasting stage, a passport is designed with a total of 47 holes for the entire section, in which 21 tons will be extracted per blasting. For ventilation, a mixed system (air injection and extraction) is proposed. On the other hand, for transportation, it is proposed to implement wagons with a capacity of 2.60 tons of lateral emptying; for the fortification, a mesh system with 25mm bolts was determined, and finally, for lighting, a system with LED strips was chosen. Finally, three sections were obtained in the tunnel extension, extracting a total of 4068 tons. Once all the project activities were defined, a work schedule was prepared for the ade-quacy (dismantling, excavation, fortification, and installation of auxiliary services), with a duration of 76 days, and for the continuation of the gallery in 90 days, giving a total of 7 months and 19 days, consequently the investment to be covered by the company to meet this end is $415,686.50. Keywords: Mining, underground works, tunnel, schedule and investment.